Hukum Melakukan Promosi Produk Overclaim Oleh Influencer Ditinjau Dari Perlindungan Konsumen (Studi : Produk Skincare): The Law on Influencers Making Overclaimed Product Promotions from a Consumer Protection Perspective (Study: Skincare Products) - vidia; Rokan, Mustapa Khamal (Jurnal Media Hukum, 2025)
Overclaiming is a practice of guaranteeing excessive and unrealistic claims. This practice not only harms consumers but also violates the basic principles of consumer protection law. This study aims to analyze the legal liability of influencers who promote products that are found to overclaim, based on the legal framework in Indonesia, specifically through a normative approach to various legal instruments. Consumer protection in this case is not limited to Law Number 8 of 1999 concerning Consumer Protection (UUPK), but also includes the Electronic Information and Transactions Law (ITE), the BPOM Regulation, and the Indonesian Advertising Ethics (EPI), which are material sources of law. The results of the study indicate that overclaiming violates the principles of good faith, fairness, transparency, and legal certainty. Influencers, as part of the marketing system, can be held legally accountable through civil, criminal, and administrative proceedings. Therefore, the results of this analysis confirm that influencers must also be held accountable because influencers cannot be considered merely passive parties, but are legal subjects who share promotional content disseminated to the public through social media. Law enforcement against influencers who make overclaims is important to provide more effective consumer protection.